The effects of increasing dosages of narasin on ruminal fermentation patterns, bacterial community composition, and nutrient digestibility in beef cattle receiving feedlot diets - Ana Laura Januário Lelis; Leandro Aparecido Ferreira da Silva; Daniel Moretto Casali; Tiago Leiva; Murilo Chuba Rodrigues; José Paulo Roman Barroso; Pedro Veloso Facury Lasmar; Camila Lisboa Tomaz; Anabelle Jorge Barbosa; Camila Cesario Fernandes Sartini; Johnny Maciel de Souza; Danilo Domingues Millen (PLoS ONE, 2026)
This study evaluated the effects of increasing narasin doses on ruminal fermentation, nutrient digestibility, ruminal pH stability, papillae histology, and microbial composition in Angus cattle fed feedlot diets. Three rumen-cannulated Angus steers (average body weight: 680 kg) were assigned to a 3 × 3 Latin square design and received diets containing 13, 20, or 27-ppm of narasin. Each experimental period consisted of 14 days of adaptation followed by seven days of sampling. Ruminal degradability was assessed on days 15–17, apparent digestibility on days 15–19, continuous ruminal pH on days 19–20, and samples for short-chain fatty acids (SCFA), microbiota, and ruminal histology were collected on days 20 and 21. Ruminal degradability was not affected by narasin dose. Digestibility of acid detergent fiber (ADF) was significantly influenced, with the greatest values observed at 27-ppm ( P = 0.01). Increasing narasin doses improved ruminal pH stability, as indicated by a linear increase in minimum pH ( P = 0.01) and a reduction in the duration of pH below 5.6 ( P = 0.10). At 13 ppm, SCFA production, particularly acetate and propionate, increased ( P < 0.05), indicating enhanced fermentation efficiency. In contrast, supplementation with 27-ppm reduced ammonia ( P < 0.01), acetate ( P = 0.02), and butyrate ( P < 0.01) concentrations and increased the acetate-to-propionate ratio ( P < 0.01). Lactate concentration decreased linearly with increasing narasin doses ( P = 0.03). Narasin supplementation altered ruminal microbial composition, increasing the relative abundance of Lachnospiraceae and Isotricha while reducing lactic acid–producing bacteria. In terms of ruminal morphology, supplementation with 20-ppm of narasin increased the keratin layer thickness of ruminal papillae ( P = 0.02), suggesting enhanced epithelial development. Overall, narasin supplementation modulated ruminal function and microbial ecology, with doses between 13 and 20-ppm providing the most favorable balance between fermentative efficiency and ruminal health in feedlot cattle.